If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -9(1 + -6p) + 3(2 + -4p) = 0 (1 * -9 + -6p * -9) + 3(2 + -4p) = 0 (-9 + 54p) + 3(2 + -4p) = 0 -9 + 54p + (2 * 3 + -4p * 3) = 0 -9 + 54p + (6 + -12p) = 0 Reorder the terms: -9 + 6 + 54p + -12p = 0 Combine like terms: -9 + 6 = -3 -3 + 54p + -12p = 0 Combine like terms: 54p + -12p = 42p -3 + 42p = 0 Solving -3 + 42p = 0 Solving for variable 'p'. Move all terms containing p to the left, all other terms to the right. Add '3' to each side of the equation. -3 + 3 + 42p = 0 + 3 Combine like terms: -3 + 3 = 0 0 + 42p = 0 + 3 42p = 0 + 3 Combine like terms: 0 + 3 = 3 42p = 3 Divide each side by '42'. p = 0.07142857143 Simplifying p = 0.07142857143
| Y(-2)=5(-4)-7 | | -8x^2+7+8=0 | | 5(2x-3)-2(x+4)= | | -8x^2+8x+9=0 | | -13-(-10)= | | 330+25h=455 | | Y(-2)=5(-2)(-2)-7 | | 15-19= | | (-5)(-14)= | | 3x+26=11x-40 | | y(1)=4(1)(1)-6(1)+3 | | 8x-24=74 | | 6c+20c= | | (12x+5)+(7x-6)= | | y(0)=5(0)(0)-7 | | x^3+4x^2-5x+2=0 | | 5.7x-2=4.7x | | -6=-10 | | x^3+x^2+x=3 | | y(1)=7(1)(1)-3(1)+1 | | 8x-5y=4y | | (-2)+w=-9 | | x+-9=-15 | | 4(-9x+5)=11(7x-6) | | -6=11+j | | 5(X+RY)=20 | | 8=h-3 | | 551+32j=615 | | b+10=2 | | 4.2x=-4(0.6x-1.2) | | (-9)+r=17 | | [2x-5]=x+4 |